2015
DOI: 10.1016/j.ymgme.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Losartan increases bone mass and accelerates chondrocyte hypertrophy in developing skeleton

Abstract: Angiotensin receptor blockers (ARBs) are a group of anti-hypertensive drugs that are widely used to treat pediatric hypertension. Recent application of ARBs to treat diseases such as Marfan syndrome or Alport syndrome has shown positive outcomes in animal and human studies, suggesting a broader therapeutic potential for this class of drugs. Multiple studies have reported a benefit of ARBs on adult bone homeostasis; however, its effect on the growing skeleton in children is unknown. We investigated the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
3
17
0
2
Order By: Relevance
“…2d and e). These data are important as a dramatically blunted snout is prevalent at a relatively early age in IDUA −/− mice (12 weeks) (Clarke et al 1997) as well as are in agreement with another murine model with losartan that showed beneficial effects to the skeleton (Chen et al 2015). …”
Section: Discussionsupporting
confidence: 84%
“…2d and e). These data are important as a dramatically blunted snout is prevalent at a relatively early age in IDUA −/− mice (12 weeks) (Clarke et al 1997) as well as are in agreement with another murine model with losartan that showed beneficial effects to the skeleton (Chen et al 2015). …”
Section: Discussionsupporting
confidence: 84%
“…The initiation of VEGF translation is enhanced by angiotensin II in an Akt-dependent manner (Feliers et al, 2005). Consistent with this, treatment of mice with an angiotensin receptor blocker leads to expansion of the hypertrophic chondrocyte zone of the growth plate (Chen et al, 2015a). However, c-Raf ablation did not alter p-Akt levels in cultured chondrocytes (Fig.…”
Section: Chondrocyte-specific Ablation Of C-raf Impairs Vascular Invasupporting
confidence: 57%
“…AT1 reseptörünün losartan ile blokajının anti-inflamatuvar ve anti-osteoklastik etkiler gösterdiği böylelikle alveolar kemik kaybını önlediği gösterilmiştir (48). Anjiyotensin yolağının losartan aracılı inhibisyonu ile kemik kütlesinin arttığı ve iskelet gelişimi sırasında büyüme plakasında kondrosit hipertrofisini hızlandırdığı gösterilmiştir (49). Daha önce yapılan bir çalışmada renal hasarlanmada losartan tedavisinin TBARS seviyelerini düşürdüğü ve KAT aktivitesinde artışı tetiklediği gösterilmiştir (44).…”
Section: Discussionunclassified